Limit equilibrium method and finite element method in slope stability analysis - Ahmad, Izwan Shah (2012)
Limit equilibrium method (LEM) has been applied for decades in slope stability analysis due to its simplicity. Various methods of analysis are available as foundations for limit equilibrium approach such as Ordinary, Bishop, Janbu, Morgenstern-Price, Spencer and others. Between these methods, there are differences in terms of assumptions made regarding interslice forces. As the technology developed and the need for a more advance method of analysis grows, finite element method (FEM) was introduced. This method is able to run rigorous analysis on complex problems. With the differences both methods possess, sensitivity analyses and comparisons of result were done using Slope/w and Plaxis software for LEM and FEM respectively. Analyses were done based on a case study of a slope located in Universiti Teknologi Malaysia (UTM) Varying parameters used in this study are cohesion, friction angle and depth of groundwater table. It is found that both programs are sensitive towards changes in friction angle where Slope/w and Plaxis indicated an increment of 32.38% and 28.20% increment respectively in terms of factor of safety. Results also showed that factors of safety obtained from LEM are higher than FEM. This is generally because finite element method can effectively calculate stresses at the crest and toe of the slope. Generated mesh using finite element method also results in a more accurate calculation as each deformation that occurs is analysed by the mesh.